Mannitol production from glycerol by resting cells of Candida magnoliae - Khan, Asiya; Bhide, Amey J.; Gadre, Ramchandra V. (Bioresource Technology, 2009)
Production of mannitol from glycerol by resting cells of Candida magnoliae under aerobic condition was investigated. The resting cells were Suspended in aqueous Solution of glycerol in Erlenmeyer flasks and incubated on rotary shaker. The samples were analyzed by ion exclusion-HPLC equipped with refractive index and UV detector. The resting cells of C. magnoliae produced mannitol from fructose, Sucrose and glycerol but not from glucose. Addition of yeast extract and/or potassium phosphate to the glycerol solution adversely affected its conversion to mannitol. The conversion of glycerol to mannitol was dependent on oxygen availability. Using testing cells, the yield of mannitol was as high as 45%. This is probably the first report of conversion of glycerol to mannitol by osmophilic yeast. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Candida magnoliae; Glycerol; Mannitol production; Resting cells